Development of a western blot method for detection of fish ectoparasite Argulus siamensis antigens. Issue 4 (4th July 2018) - Das, P.; Mohanty, J.; Badhe, M.R.; Sahoo, P.K.; Sardar, K.K.; Parija, S.C.
ABSTRACT: A study was undertaken to develop a western blot method for detection of immunogenic proteins of fish ectoparasite, Argulus siamensis for its further use as potential vaccine candidates. Argulus antigens were prepared by homogenization and injected to rohu ( Labeo rohita ) juveniles for development of immune serum. The serum was used to immunostain the antigens in western blot. The other reagents added in sequence were rabbit anti-rohu serum, goat anti-rabbit ALP conjugate and substrate (BCIP-NBT). However, similar banding patterns were observed with both control and immunized rohu serum. Hence, a possible cross-reaction was suspected and verified in number of western blot experiments. A typical cross-reaction observed was of rabbit serum reacting directly with Argulus antigens. Hence, the rabbit anti-rohu serum was replaced with guinea pig anti-rohu serum. Another cross-reaction of goat anti-guinea pig ALP conjugate with rohu serum was eliminated by using goat anti-rabbit ALP conjugate with guinea pig serum. Thus, the final western blot method consisting of Argulus antigens → rohu serum → guinea pig anti-rohu serum → goat anti-rabbit ALP conjugate → substrate, yielded distinguishing results between control and Argulus -immunized rohu serum samples. The developed test has tremendous downstream applications, particularly in immunoproteomic studies of Argulus antigens.